Scope of Global Citizenship Education in the National Curriculum Framework 2021 of Bangladesh: A critical Review (Teacher’s World: Journal of Education and Research, 2024)
Global Citizenship Education (GCED) has significant role in creating active and responsible citizens with specific knowledge, skills, and values – such as solidarity, tolerance, empathy who can address the challenges of future uncertain world. This study aims to explore the scope of GCED in the new National Curriculum Framework (NCF) 2021 of Bangladesh. Qualitative content analysis was used to critically analyze the NCF as a document. The findings show that the NCF has created a great deal of opportunities for infusing GCED in the curriculum mainly in four aspects. First, it has stepped into competency based education which is one of the major preconditions for embedding GCED in the curriculum framework. Second, within the development process, it created the scope of addressing GCED issues and discourses. Third, in conceptualizing different aspects of the curriculum such as, conceptual understanding of the curriculum within a theoretical framework proposed, the understanding of the competency-based curriculum, assessment system, and technical aspects of the education system, GCED concepts were projected heavily. Fourth, learning area wise core competencies and the subject-wise competencies also clearly reflect the GCED knowledge, skills, and values. However, analysing the NCF from ‘soft’ and ‘critical’ GCED perspective, we found that though the NCF focused both ‘soft’ (e.g., harmony, tolerance, humanity, empathy, human rights, self-awareness) and ‘critical’ (e.g., social justice, creative and critical thinking, power and governance, informed and reflective action) GCED perspectives, it is leaned towards the ‘soft’ GCED aiming to create active citizens who will be able to solve the problems of the world to live a better life, not challenging the existing social and underlying power structure, which is more of a ‘critical’ GCED perspective. Explicit mention of GCED theories, approaches and tools such as gender transformative approaches, process of involving the disadvantaged groups in the NCF development process would make GCED attributes more visible in the document. This study will help the researchers, policy-makers, and educators to bridge this policy document with detailed curriculum, textbooks, and teacher professional development programs to understand the status of translation of GCED to create responsible national and global citizens.Teacher’s World: Journal of Education and Research, 49 (1), 49-76